Aplikasi Konsep Understand, State, Evaluate, Plan, Do, Study, Action - Handayani, Dwi Iryaning (Department Industrial Engineering, University of Muhammadiyah Malang, 2007)
Tiang pancang is the main product of PT Hume Sakti Indonesia. There were the error product of it,the company must be found the solution which can be used to increase quality of this product itself. The writer wanted to plain the improvement of product quality with using USE-PDS concept (Understand, State, Evaluate, Plan, Do, Study, Act) and FMEA analysis. After the writer have done this concept and FMEA got the result where the first DPMO for this company was 10853 per billion of chance with total of failure was 5.680.000 rupiahs. Than chose alternative which the writer can be recommended based on the FMEA table, where recommendation to choose this alternative based on the highest value. Based on FMEA table was gotten the highest priority was from the last production.